The essential Lewis & Clark - Lewis, Meriwether, 1774-1809; Clark, William, 1770-1838 (National Geographic, 2018)
"The celebrated journals of Lewis and Clark's legendary expedition into the uncharted American West, abridged into a single volume and translated into modern English, with nuanced observations from star author and journalist Anthony Brandt. At the start of the 19th century, Meriwether Lewis and William Clark embarked on an unprecedented voyage of discovery. Their assignment was to explore the newly acquired Louisiana Territory and record the geography, flora, fauna, and people they encountered along the way. This updated edition of the captains' journals combines historical insight from editor Anthony Brandt with the rich detail of Lewis and Clark's original writing, as well as archival maps and artwork. An enthralling portrait of the unspoiled West, this true-life adventure story is a window to the dawning of America--from encounters with grizzly bears to councils with tribal leaders and perilous mountain crossings."--Provided by publisher.